2023
DOI: 10.1039/d2en00446a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the design of controlled- and sustained-release micro/nanocarriers of pesticide

Abstract: Diagram of components of controlled- and sustained-release micro/nanocarriers of pesticide: nanomaterials and stimuli-responsive triggers (R stands for different groups).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 148 publications
0
16
0
Order By: Relevance
“…Even though some reviews related to MOF-based nanoplatforms in the agriculture field have been reported, in this review, we mainly focus on the progress of MOF-based nanoplatforms for crop protection, including phytopathogen, pest, and weed control and crop growth promotion, including fertilizer/plant hormone delivery (Scheme ). The principal design, mechanisms, effectiveness, and advantages of MOF-based nanoplatforms in crop protection and growth promotion are emphasized through systematically investigating the representative research work.…”
Section: Introductionmentioning
confidence: 99%
“…Even though some reviews related to MOF-based nanoplatforms in the agriculture field have been reported, in this review, we mainly focus on the progress of MOF-based nanoplatforms for crop protection, including phytopathogen, pest, and weed control and crop growth promotion, including fertilizer/plant hormone delivery (Scheme ). The principal design, mechanisms, effectiveness, and advantages of MOF-based nanoplatforms in crop protection and growth promotion are emphasized through systematically investigating the representative research work.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the application of nanomaterials and/ or nanotechnology during agrochemical processing, also referred to as nanopesticide, has been proven to be a promising approach for reducing the loss of bioactive components in herbicides and the harmful effects of herbicides on the environment, 17,18 especially for those cases of nano-scale carriers converted from sustainable natural materials. [19][20][21] As one of the abundant and available marine biomass materials, chitosan (Cs) can serve as a candidate carrier for loading bioactive compounds and sustained release applications.…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges facing the agricultural field is low crop yields, where fungi, viruses, harmful insects, and organisms can all affect food production. , So far, pesticides that have quick action properties effectively safeguard crops against pests and diseases, resulting in a significant increase in crop yields by up to 30 to 40%. , However, conventional pesticide formulations still face significant drawbacks, including low adhesion to target foliar surfaces, short effective time in the field, nontarget toxicity, and negative environmental impacts. , Consequently, reducing the quantity of pesticide applications without compromising their effectiveness is a crucial issue that needs to be addressed. Fortunately, controlled and slow-release micro/nanocarriers can meet the challenge of pesticide misuse …”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, controlled and slow-release micro/nanocarriers can meet the challenge of pesticide misuse. 8 In the field of drug delivery, a variety of materials have been used to load drug and reduce drug losses, including organometallic frameworks, 9 biochar, 10−12 organic polymers, 13,14 and silica carriers. 15 Among them, mesoporous silica is widely employed in the delivery of nanopesticides because of its affordability, easy modification, large specific surface area, and favorable biocompatibility.…”
Section: ■ Introductionmentioning
confidence: 99%